Fulfillment employment rights for individuals with disabilities in Surabaya - Purba, Iman Pasu; Tauran, Tauran; Widianti, Alifia; Lianna, Irma (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
This research is a type of socio-legal research with a qualitative approach that, in collecting data, uses two types of data sources: primary from interviews with informants and secondary obtained from reading book searches and product analysis of applicable laws and regulations related to persons with disabilities. This study aims to determine the extent to which the fulfillment of the right to work for persons with disabilities has been carried out in the City of Surabaya by the City Government through the performance of authorized regional institutions and the underlying legal products. This research is a topic that is quite important and has urgency today because, considering the increasingly rapid current of modernization now, it does not necessarily improve the quality of fulfilling human rights (HAM), especially for people with disabilities, who often receive discrimination from the surrounding environment, especially in the field of work. In the field of work, persons with disabilities have the same rights as non-disabled workers, as explained in the 1945 NRI Constitution Article 28D Paragraph (2). A derivative of the reading of the Article of the Constitution is in Law Number 13 of 2003 concerning Manpower, which also discusses employment rights for persons with disabilities. In the future, Local Regulation to protect disabled persons is needed.